Insights into the Genetic Architecture of Diabetic Nephropathy - Palmer, Nicholette D. (2012)
Diabetic nephropathy (DN) is a devastating complication of type 1 and type 2 diabetes and leads to increased morbidity and premature mortality. Susceptibility to DN has an inherent genetic basis as evidenced by familial aggregation and ethnic-specific prevalence rates. Progress in identifying the underlying genetic architecture has been arduous with the realization that a single locus of large effect does not exist, unlike in predisposition to non-diabetic nephropathy in individuals with African ancestry. Numerous risk variants have been identified, each with a nominal effect, and they collectively contribute to disease. These results have identified loci targeting novel pathways for disease susceptibility. With continued technological advances and development of new analytic methods, additional genetic variants and mechanisms (e.g., epigenetic variation) will be identified and help to elucidate the pathogenesis of DN. These advances will lead to early detection and development of novel therapeutic strategies to decrease the incidence of disease.